A new animal-borne imaging system for studying the behavioral ecology of small sharks: laboratory and field evaluations. Issue 3 (3rd May 2020) - P. O'Connell, Craig; Collatos, Caroline; Picha, Nicholas D.; He, Pingguo
ABSTRACT: The use of animal-borne imaging and environmental data collection systems (AVEDs) can provide behavioral and ecological information of animals that many other technologies cannot usually offer. However, many previous AVEDs have been designed for larger sharks, and there is a need for a technology that permits the collection of behavioral and ecological data for small sharks. In this study, we developed and tested the Shark Harness, a novel AVED technology for small to medium size sharks, in both the laboratory and the field. In the laboratory, the swimming behavior of seven dusky smoothhound sharks ( Mustelus canis ; n = 7) ranging in size from 90.00–114.30 cm total length (TL) was assessed. When compared to unmanipulated individuals, sharks fitted with the Shark Harness exhibited no significant variations in both swimming duration (p = 0.63) and vertical positioning (0.99), whereas a minor, yet statistically significant, increase in tail beat frequency (p = 0.016) was observed. In the field, six dusky smoothhound sharks (90–110.28 cm TL) equipped with the Shark Harness were released in waters near Montauk, New York, USA. Field data suggest that the Shark Harness can be used to assess fine-scale movements, heterospecific interactions, and immediate post-release survivorship of dusky smoothhound sharks and other small sharks (≥80 cm TL) in a wild setting. However, future modifications are required prior to redeployment in a wild setting, including a more cryptic and hydrodynamic design, in order to obtain a more accurate representation of the respective animal's natural behavior and interactions with con- and hetero-specifics.